ANSWER
The correct factorization is
[tex]p^{3} - 343q^{3} = (p - 7q)( {p}^{2} + 7pq + {49q}^{2} )[/tex]
EXPLANATION
The given expression is
[tex] {p}^{3} - 343 {q}^{3} [/tex]
We can write this as difference of cubes.
[tex]{p}^{3} - {7}^{3} {q}^{3} [/tex]
[tex]{p}^{3} - ( {7} {q})^{3} [/tex]
We can now factor using the difference of cube identity:
[tex] {x}^{3} - {y}^{3} = (x - y)( {x}^{2} + xy + {y}^{2} )[/tex]
We substitute x=p and y=7p to get:
[tex]{p}^{3} - ( {7} {q})^{3} = (p - 7q)( {p}^{2} + p \times 7q + ({7q})^{2} )[/tex]
[tex]{p}^{3} - ( {7} {q})^{3} = (p - 7q)( {p}^{2} + 7pq + {49q}^{2} )[/tex]